VD_FINDINFO Arrêt / 2017 / 1033 vom 6. März 2018 - VD Tribunal cantonal (2018)
PÉRIODE DE COTISATIONS, DÉLAI DE RÉSILIATION, INCAPACITÉ DE TRAVAIL | 336c CO, 13 LACI, 9 al. 1 LACI, 9 al. 3 LACI, 11 OACI